Evaluation of Curcuma longa L. on chronic leukaemia rats: serum biochemistry parameters and urinalysis - M. Y., Yusnaini; Hamzah, Hazilawati; Shaari, Mohd Rosly; Sabri, Jasni; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin; Haron, Nursyuhada; Mohd Zairi, Nurul Huda (2012)
The objective of this study was to evaluate the preventive effects of Curcuma longa L. in MNU-induced chronic leukaemia in rats via examination of blood biochemistry parameters and urinalysis results. A total of 64 male Sprague Dawley rats were divided into four groups (n=16). Leukaemia was induced in 32 Sprague Dawley rats via administration of N-Methyl-N-Nitrosourea (MNU), intraperitoneally, at a dose of 60 mg/kg of body weight for four times within a two-week period at the beginning of the experimental period. Sixteen leukaemic and 16 control rats were daily supplemented with 5000 mg/kg of dried C. longa L. started at week 0. All the rats were sacrificed at week 20 after administration of MNU and/or received daily supplementation of C. longa L.. Blood samples of all rats were collected into blood tubes with no anticoagulants for serum and analysed for liver and kidney biochemistry parameters by using an automated biochemistry analyser. Urine samples were collected at 12 hours fasting condition in metabolic cages for further assessment of kidney function. Results showed that all serum biochemistry and urinalysis parameters of leukaemic rats and leukaemic rats supplemented with C. longa L. were not significantly different from control. Although the results were statistically no difference from control, some of the parameters include urine protein to creatinine ratio (UPC) and creatinine clearance showed slight changes and may be useful as important parameters for early detection of renal function impairment. In conclusion, serum biochemistry and urinalysis parameters could not be solely used as tools in evaluating the preventive effects of C. longa L. in leukaemic rats at 20 weeks of experimental period.